Pre‐Processing MALDI/TOF Mass Spectra by Using Geena 2. Issue 1 (13th November 2018) - Romano, P.; Profumo, A.; Facchiano, A.
Abstract: Geena 2 is a tool for filtering, averaging, and aligning MALDI/TOF mass spectra, designed to assist scientists in the analysis of high volumes of data and support them for comparative studies. Three web interfaces are available with different levels of complexity. In this manuscript, we explain how to use Geena 2 with these three interfaces to perform analyses of one's own data. Two support protocols showing how to check the example input file and how to create an input file with own data are also presented. © 2018 by John Wiley & Sons, Inc.